EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT (TGT) DAN TEAM ASSISTED INDIVIDUALIZATION (TAI) PADA MATERI KPK DAN FPB DITINJAU DARI TINGKAT KECERDASAN LOGIKA MATEMATIKA SISWA KELAS V SD NEGERI SE-KECAMATAN PURWODADI TAHUN PELAJARAN 2 - W, Kharisma Ardhy; Budiyono, Budiyono; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aim of the research was to find out the effect of learning models on mathematics achievement viewed from the student logical-mathematical intelligence in the topic of Smallest Common Multiple (SCM) and Greatest Common Factor (GCF) at fifth grade students of elementary schools in Purwodadi District. The learning models compared Teams Games Tournament (TGT), Team Assisted Individualization (TAI), and direct instruction model. The type of the research was a quasi-experimental research. The population was the students at fifth grade of Elementary School in Purwodadi District on academic year 2013/2014. The size of the samples were 192 students consisted of 87 students in the first experimental group by using cooperative learning model Teams Games Tournament (TGT), 53 students in the second experimental group by using cooperative learning model Team Assisted Individualization (TAI), and 52 students in the control group by using direct instruction model. The instruments used mathematics achievement test and logical-mathematical intelligence test. The data was analyzed using two-way analysis of variance. The conclusions of the research were as follows. (1) TGT model gives mathematics achievement as well as TAI, whereas TGT and TAI model gives better mathematics achievement than the direct instruction model. (2) The high logical-mathematical intelligence students have better mathematics achievement than middle and low logical-mathematical intelligence students and the middle logical-mathematical intelligence students have better mathematics achievement than the low logical-mathematical intelligence students. (3) For all types of logical-mathematical intelligence students, TGT model gives mathematics achievement as well as TAI, whereas TGT and TAI model gives better mathematics achievement than the direct instruction model. (4) For all types of learning model, the high logical-mathematical intelligence students have better mathematics achievement than middle and low logical-mathematical intelligence students and the middle logical-mathematical intelligence students have better mathematics achievement than the low logical-mathematical intelligence students.Key words: Teams Games Tournament (TGT), Team Assisted Individualization (TAI), logical-mathematical intelligence, learning achievement.